The Effectiveness of a Learning Strategies Course on College Student-Athletes' Adjustment, Use of Learning Strategies, and Academic Performance - Tebbe, Carmen M.; Petrie, Trent A. (My University, 2006)
We examined the effectiveness of a learning strategies course in assisting at-risk male and female freshmen student athletes in improving their academic performances. Participants included 129 freshman student-athletes (Female=72 and Male= 57) from a large southern university. Eighty-six participants were enrolled in the student-athlete PSYC 1000 class, either in Fall 2003 or Fall 2004; 43 were student-athletes who entered the university during the same time but were not required to enroll in the course because their test scores and high school grades met or exceeded the university's academic requirements for open admission. The learning strategies course (PSYC 1000) is based on psychological and educational theories and models associated with learning, self-regulation, personal and career development, communication, stress and coping, and health. The overall goals of the course are to (1) assist students in developing effective strategies to be proficient learners, (2) increase their understanding of how people change and develop, and (3) apply this knowledge across academic programs and in all areas of their lives to make positive, self-enhancing changes. The course was based on the same syllabus and lesson plans that are used in other PSYC 1000 sections for students who are not athletes, however, the lesson plans are tailored to encompass the specific demands of the student-athlete experience. The at-risk student athletes reported improvements across a wide range of study skills, such as comprehension, concentration and use of test-taking strategies, during their first semester of college when they were enrolled in the course. In comparison to regularly admitted student-athletes who did not take the course, the at-risk student athletes earned comparable grades during their first two semesters. Although neither academic nor noncognitive variables predicted the male student athletes' first and second semester GPA's, female athletes' ability to manage their time as well as their willingness to take responsibility for their learning was positively related to their academic performances. Regarding their adjustment to college, the at-risk student athletes showed improvement in the personal/emotional area, but slight decreases with respect to academics and social relationships. Overall, these findings support learning strategies courses as an effectiveness mechanism for improving the academic performance of at-risk student athletes.
Keywords: skills; freshmen; transitions